Conceptualizing culture in research on parenting and child development: carving, categorizing, and communicating pathways. Issue 2 (3rd April 2021) - Suizzo, Marie-Anne
Abstract: In this paper, I propose a conceptualization of culture as a set of processes involving pathways of acting in the world. These cultural processes are: (1) choosing existing pathways or carving out new ones, (2) attaching meanings to and categorizing pathways, and categorizing people according to their movement on pathways, and (3) communicating about shared pathways with each other and with others on different pathways. I explicate this conceptualization and illustrate these cultural processes with research in the areas of children's and adolescents' development and parent-child relationships. I then offer suggestions for future research and applications for practitioners in line with the cultural processes outlined in this conceptualization.